A critical review of social and health inequalities in the nursing curriculum. (March 2017) - Rozendo, Célia Alves; Santos Salas, Anna; Cameron, Brenda
Abstract: Context: Social and health inequalities are a reality around the world and one of the most important challenges in the current age. Nurse educators can respond to these challenges by incorporating curricular components to identify and intervene in social and health inequalities. Objective: To examine how social and health inequalities have been addressed in the nursing curriculum. Design: Informed by the work of Paulo Freire, a critical literature review was performed to examine how social and health inequalities have been addressed in the nursing curriculum. Data Sources and Review Methods: In July 2015, we searched for articles published from 2000 to 2015 in ERIC, CINAHL, Web of Science, Scielo, MEDLINE and LILACS databases. Main search terms included "disparity" or "inequality" and "curriculum" and "nursing." We included studies published in academic journals in English, Portuguese and Spanish. Results: A total of 20 articles were included in this review. Most of the articles (15) were from the United States and described educational experiences in implementing courses in nursing undergraduate curricula. Limited experiences with graduate nursing education were identified. Social and health inequalities were approached in these articles through elements such as social justice, cultural competence, cultural safety, and advocacy. A concern to reduce social and health disparities was noted. We identified three major themes in the articles included in this review: 1) elements in the curricula that can contribute to reducing social and health inequalities; 2) educational and research strategies used to address the theme of inequalities; 3) a focus on socially vulnerable populations to increase awareness on social and health inequalities. Conclusion: Findings suggest that nursing education initiatives align with the recommendations from the World Health Organization to address disparities. There is also a need to identify existing conceptual and practical content on inequalities in the nursing curriculum through future research. Highlights: Social and health inequalities are one of the most important challenges today. Nurse educators need to engage in practices that address inequalities. Nurses are in a position to tackle global inequalities in their practice. Nursing curricula must incorporate specific elements to reduce inequalities.